Imagens de morte como manifestação do erótico - Rodrigo Freitas Rodrigues (2011)
This research investigates the possible relationships between death and eroticism in the field of image. Such statements are based on the theories of the French philosopher Georges Bataille, for whom eroticism, death and religion are three inseparable mankinds aspects manifested in art. On the first chapter there will be a brief history of Western philosophical thought, in order to demonstrate how the human being have faced and even thought about death over the time. To get into Batailles thoughts, it is necessary to investigate the notions of holiness, excess and play. The second chapter deals more specifically with the relationship between eroticism and death from specific examples of Art History. The considerations on eroticism in this chapter are based on the studies of the Italian philosopher Mario Perniola, who extends the discussions proposed by Georges Bataille. This chapter focuses on the relationship between dress and undress. It starts with the rhetorical formulations that legitimated the existence of images such as the naked dead body of Christ in the context of the XVI century, and finally consider the body itself as a robe. That robe can be either the flesh, as evidenced by considerations of Tertullian and the anatomical drawings of the XVI century, or the host body, proposed by Klossowski. On the way from the naked body to the clothes, and from the clothes toward the body as a garment for the spirit, it is possible to identify the strategies of preventing images from iconoclastic threats. The proposed relationship between death and eroticism, bring into light fundamental discussions about Art History. The third chapter investigates the work of Felix Gonzalez Torres, who provides constant relationship between death and eroticism as well as investigates the very status of the image. Observing some of his works is possible to establish connections with the Georges Batailles thoughts.